2019
DOI: 10.1590/s2175-97902019000117561
|View full text |Cite
|
Sign up to set email alerts
|

Short-term high-fat diet affects macrophages inflammatory response, early signs of a long-term problem

Abstract: Obesity is a chronic inflammatory disease that affects millions of people worldwide. Most studies observe the effects of a high-fat diet (HFD) in 10-12 weeks. This work investigated the effects induced by a HFD administered for 6 weeks on the nutritional status of mice and some aspects of the inflammatory response in mouse peritoneal macrophages. Male Swiss Webster mice, 2-3 months of age, were fed a control diet or HFD for 6 weeks. After this period, the mice were euthanized, and peritoneal macrophages were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
6
4
0
Order By: Relevance
“…The present study also denoted increased IL-6, IL-1β and TNF-ɑ levels which can function as inflammatory cytokines. Our results were parallel to those obtained by Wang and He, 2018 , Campbell et al, 2019 , Santos et al, 2019 . Induction of obesity and accumulation of fat usually accompany dysfunctional lipid metabolism, including extensive lipolysis, which in turn increases secretion and production of free fatty acids (FFAs).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study also denoted increased IL-6, IL-1β and TNF-ɑ levels which can function as inflammatory cytokines. Our results were parallel to those obtained by Wang and He, 2018 , Campbell et al, 2019 , Santos et al, 2019 . Induction of obesity and accumulation of fat usually accompany dysfunctional lipid metabolism, including extensive lipolysis, which in turn increases secretion and production of free fatty acids (FFAs).…”
Section: Discussionsupporting
confidence: 91%
“…In present study, the feed intake in HFD group was significantly reduced than control, however, weight gain increased as well as relative fat mass due to high dietary fat content. These results were in harmony with the records of Santos et al, 2016 , Santos et al, 2019 , Kostrycki et al, 2019 . The possible attribution is that higher energy intake in HFD group caused promotion of weight gain consequent to the increased fat mass.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is critically important to understand that obesity is associated with macrophage accumulation in adipose tissue 33 , 34 . It has been reported that diet‐induced obesity activates adipose tissue macrophages (ATM) into pro‐inflammatory M1 macrophages that produce a variety of pro-inflammatory cytokines such as TNF‐α and IL‐6, which contribute to the development of diabetes and atherosclerosis 35 , 36 . In our study, in line with previous studies, MSC administration lowered the expression of pro‐inflammatory cytokines 37 , 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted at the Embryology Laboratory of the Faculty of Veterinary Medicine, Universitas Airlangga within a period of 5 months (July to November 2019). Experimental animals were placed at room temperature 25 ± 2°C with a humidity of 50-60% and the lighting was regulated by a light-dark cycle with the regulation of 12 hours of light and 12 hours of darkness (Anandakumar et al, 2009;Gao et al, 2011;Santos et al, 2019;Pinthong and Suanarunsawat, 2020;Wunjuntuk et al, 2020). Mice cages measuring 30x45x20 cm, made of plastic covered with gauze equipped with a place to eat and drink bottles, each cage is filled with 1 group (6 mice).…”
Section: Animals Diets and Experimental Protocolmentioning
confidence: 99%